Surfactant Protein C Expression in Urethane-Induced Murine Pulmonary Tumors - Mason, Robert J. (American Society for Investigative Pathology, 2000)
Mice injected with urethane develop tumors with distinct histological patterns, which are classified as solid, papillary, or a mixture of these two patterns within the same tumor. Most investigators agree that solid tumors arise from alveolar type II cells, but the cellular origin of papillary tumors is less certain, being attributed to either type II cells or nonciliated bronchiolar epithelial (Clara) cells. To characterize the state of differentiation of these tumors more precisely and to provide additional information on gene expression, we used immunocytochemistry and/or in situ hybridization to determine the cellular localization of surfactant-associated proteins A (SP-A), SP-B, SP-C, and SP-D; Clara cell-associated protein CC-10; and thyroid transcription factor-1. In normal mouse lung, the messenger RNAs (mRNAs) for SP-A, SP-B, and SP-D were expressed in both type II cells and Clara cells. SP-C mRNA, however, was expressed only in type II cells, and CC-10 expression of mRNA was restricted to Clara cells. All tumors examined, both solid and papillary, expressed SP-A, SP-B, SP-C, SP-D, and thyroid transcription factor-1, but not CC-10. However, SP-C expression was slightly diminished in larger (older) papillary tumors. These results demonstrate that urethane-induced murine lung tumors express the type II cell phenotype.